Fallen gods - Van Dyken, Rachel (Fallen gods, 2025)
"The Gods aren't dead--they're only sleeping, locked in mortal bodies, scattered across the world, waiting for the right spark to wake them. And my father is the most ruthless of them all. He raised meto obey. To bleed. To be his blade when the time came. Now he's sending me to Endir University, a place filled with ancient bloodlines and deadly secrets, to steal back Mjolnir, the hammer of legend. If I fail, everyone I love dies. But Aric Erikson wasn't part of the plan. He's the enemy's heir. Distant. Dangerous. And the one person I can't afford to fall for. He's closed himself off completely behind a wall of ice, but the more I'm ordered to unravel him, the harder it becomes to remember where the lies end and I begin"--